Pengaruh Profitabilitas, Struktur Modal, dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Subsektor Food and Beverage Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2023 - Pebrianti, Wahyu Puji; Astuti, Puji; Sugeng, Sugeng (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This research is motivated by the tight business competition and the decline in the average value of food and beverage companies in 2020-2023. The purpose of this study was to determine the effect of profitability, capital structure, and company size on firm value. This study uses a quantitative approach with secondary data. The sample in this study amounted to 19 manufacturing companies selected using purposive sampling technique. The data analysis technique was carried out by multiple linear regression analysis with SPSS for windows version 23 software. The results showed that profitability and capital structure partially affect firm value, while firm size partially has no effect on firm value. Profitability, capital structure, and company size simultaneously affect firm value. Based on the results of the analysis and conclusions obtained, it is hoped that future companies can manage their debt in order to reduce their interest expense. For future researchers, it is recommended to add other variables such as dividend policy variables and CSR. For investors, it is advisable to consider profitability and capital structure factors in making investment decisions because it is proven that they have an effect on firm value.